2012
DOI: 10.4187/respcare.01941
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Oxygen Administration by Nasal Cannula for Adult and Perinatal Patients

Abstract: The nasal cannula has been a commonly used patient interface to provide supplemental oxygen since its introduction in the 1940s. Traditionally, it has been categorized as a low-flow device and capable of delivering a 0.4 F IO 2 with flows up to 6 L/min to adults with normal minute ventilation. However, there is considerable performance variability among patients and design, which results in an exponential decline in delivered F IO 2 as breathing frequencies increase. The nasal cannula has also been successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
151
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(160 citation statements)
references
References 74 publications
1
151
0
8
Order By: Relevance
“…9,53 Extrathoracic anatomic dead space is related to age and is higher in small infants (.3 mL/kg) compared with adults. 54 Thus, continuous washout of this relatively large space with a supply of fresh gas could be of clinical benefit, especially in the neonatal period.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…9,53 Extrathoracic anatomic dead space is related to age and is higher in small infants (.3 mL/kg) compared with adults. 54 Thus, continuous washout of this relatively large space with a supply of fresh gas could be of clinical benefit, especially in the neonatal period.…”
Section: Figurementioning
confidence: 99%
“…The most recent mode of respiratory support to be introduced for newborn infants, HHHFNC, however, has quickly gained popularity among clinicians worldwide, [9][10][11][12][13] although evidence supporting its use is not fully established. [14][15][16] Several clinical trials over the last decade have collected evidence of the use of HHHFNC in preterm infants, both as a primary mode of support at birth and after extubation from MV.…”
mentioning
confidence: 99%
“…delivered flow to the patient is affected by the patient's flow pattern, such as the spontaneous inspiratory and expiratory ratio and the patient's nasal, nasopharynx, and oropharynx anatomy. 14 Acknowledging nasal cycling as a persistent physiological event throughout the day and night while keeping in mind the large population of individuals using a nasal cannula for oxygen therapy, the primary aim of this bench study is to evaluate the effects of nasal cycling on the delivered F IO 2 during oxygen administration via nasal cannula at various therapeutic flows to an anatomic model. Additionally, a thorough review of the literature revealed no previous studies comparing right and left prong oxygen flow for nasal cannula adjuncts at various therapeutic flow settings.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…3,4 The nasal cannula is one of the most common oxygen delivery adjuncts used when delivering supplemental oxygen. 14 The nasal cannula is a plastic, disposable, lowflow device used to deliver up to 6 L/min of oxygen. 15 It consists of 7 or 14 feet of crush-resistant small bore oxygen tubing and 2 prongs that are approximately 1 cm in length, which are placed directly into the patient's nares.…”
Section: See the Related Editorial On Page 565mentioning
confidence: 99%
“…If the patient receives FiO 2 of greater than 60% and more than 48 hours, the patient may at risk of oxygen toxicity. Positive pressure ventilation improves oxygenation and CO 2 removal by alveolar recruitment, increasing alveolar volume and redistribution of extracellular lung water, So it is reasonable to use positive pressure in the patient on high O 2 like this level ( Figure 1) [2]. Epistaxis, base of skull fracture, surgery to the nose or upper aero-digestive tract, nasal obstruction; e.g.…”
Section: High Flow Oxygen Systemmentioning
confidence: 99%